Design and Simulation of Fuzzy Logic Controller for DSTATCOM in Power System - Taifour Ali, Awadalla; Bashier M. Eltayeb, Eisa; M. Bakhit, Rufidah (University of Khartoum Engineering Journal, 2022)
This paper mainly presents the Distribution Static Compensator (DSTATCOM) and control methodology of Direct Current (DC) capacitor voltage. Generally, the DC capacitor voltage is regulated using a Proportional Integral (PI) controller when various control algorithms are used for load compensation. However, during load changes, there is considerable variation in dc capacitor voltage which might affect compensation. In this study, a fuzzy logic based supervisory method is proposed to improve transient performance of the dc link. The fuzzy logic based supervisor varies the proportional and integral gains of the PI controller during the transient period immediately after a load change. A considerable reduction in the error in DC link capacitor voltage during load changes compared to a normal PI controller is obtained. The performance of the proposed strategy is proved using detailed simulation studies.